Sustainability Reporting dan Pandemi Covid-19 - Dewi, Ni Putu Yunita; Sudana, I Putu (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p02, 2022)
This study aims to determine the level of compliance with PT Perusahaan Gas Negara Tbk's Sustainability Reporting. (PGN) to the latest standards issued by the Global Reporting Initiative, namely the GRI Standards. Another objective is to find out the activities and costs of environmental social responsibility (TJSL) before and during the CoronaVirus Disease-2019 (Covid-19) pandemic. This research is a descriptive qualitative research with a case study approach at SR PT. Perusahaan Gas Negara Tbk. (PGN) in 2016-2020. The results of the study show that the percentage level of compliance of PGN's SR to GRI Standards has increased over the last 5 years. There is a change in the focus of TJSL activities at PGN in 2020, namely the focus on preventing and overcoming the Covid-19 pandemic. Due to the impact of the Covid-19 pandemic and the case of PGN's tax dispute with the Directorate General of Taxes, costs for TJSL activities decreased by 38% in 2020. Keywords: Sustainability Reporting; Covid-19 pandemic; GRI Standard, Case Study.